Implementation of Sustainable Development Goals in Mining Companies Listed on The Indonesia Stock Exchange in 2018-2020 - Acynthia Ayu Wilasittha; Sofie Yunida Putri; Rizdina Azmiyanti (Future Science, 2021)
Sustainable Development Goals (SDGs) is a global initiative designed by the United Nations General Assembly in 2015 to achieve sustainable development by emphasizing the 5Ps: People, Planet, Prosperity, Peace, and Partnership. With 17 integrated global goals, the SDGs are expected to be able to create synergy between humans and social, economic, and environmental aspects that are intended to be achieved by the year 2030. The Government of Indonesia has issued Presidential Regulation No. 59 of 2017 concerning the Implementation of Achieving Sustainable Development Goals (SDGs) to give some directions on how to implement the SDGs in Indonesia. This study aims to determine the implementation of the SDGs in mining companies in Indonesia in 2018-2020. This qualitative research uses the content analysis method using secondary data in the form of a Sustainability Report which contains disclosures of economic, environmental, and social performance. From this data, it will be analyzed whether companies in Indonesia have started implementing the SDGs and are consistently running them even during the Covid-19 pandemic. The population in this study are all mining companies listed on the Indonesia Stock Exchange from 2018 to 2020. The sampling technique in this research is purposive sampling by taking a sample of mining companies that publish a Sustainability Report.